2010
DOI: 10.1055/s-0029-1240979
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Carotid Artery for Arterial Cannulation: Side-Related Differences

Abstract: Both common carotid arteries are suitable for arterial cannulation; however, left-sided cannulation is associated with an increase in the pressure profile. Therefore, if vascular pathology does not dictate cannulation of the left carotid artery, the right carotid artery should be considered the site of choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…By using Doppler duplex scanner, Ackroyd et al [31] concluded that there was no significant difference of blood flow between the two carotid arteries in normal people. However, Urbanski et al [32] inspected the blood flow in the carotid arteries after cannulation and found that even though the flow rates were similar, the perfusion pressure was significantly higher in the left carotid than in the right carotid artery. In this study, higher occlusion rate was observed in both hypertension and in left-sidedness which seems to correlate with the phenomenon report by Urbanski et al [32] However, Schneiders et al [33] discovered that a flow diverter seems to have no effect on reducing the pressure in the aneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…By using Doppler duplex scanner, Ackroyd et al [31] concluded that there was no significant difference of blood flow between the two carotid arteries in normal people. However, Urbanski et al [32] inspected the blood flow in the carotid arteries after cannulation and found that even though the flow rates were similar, the perfusion pressure was significantly higher in the left carotid than in the right carotid artery. In this study, higher occlusion rate was observed in both hypertension and in left-sidedness which seems to correlate with the phenomenon report by Urbanski et al [32] However, Schneiders et al [33] discovered that a flow diverter seems to have no effect on reducing the pressure in the aneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…However, even though we were not able to demonstrate an advantage of the right-sided perfusion in which two brain-supplying arteries are perfused in a cohort of 200 patients, the theoretical possibility of improved cerebral perfusion through the right side cannot be completely eliminated in some very rarely seen vascular pathologies. For this reason, we consider the right-sided cerebral perfusion as the standard, especially because the right carotid artery and the innominate artery are more suitable for cannulation than the left carotid artery [23]. Nevertheless, if dictated by the patient's pathology, cannulation of the left common carotid artery and left-sided cerebral perfusion can be considered as a very effective and safe alternative.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The approach to the carotid artery is simple and fast, and especially relevant in emergency. 3 It is noteworthy that the incidence of dissection involving the carotid arteries is 28%. 4 The real-time assessment of the extent of dissection dictates the supra-aortic cannulation in such a case scenario.…”
Section: To the Editormentioning
confidence: 99%
“…1,2 Given that each modality has its own advantages and disadvantages, transesophageal echocardiography (TEE) seems to hold an edge over the gold standard pulmonary artery catheterization (PAC) in liver transplantation. 3 However, even though TEE gives a wide range of information, it still is an expensive technology, with restricted availability in most health care facilities, requires expertise to be fully exploited, and is semi-invasive in nature for use in patients with risk of variceal rupture.…”
Section: Transdiaphragmatic Echocardiography As a Rescue In Liver Tramentioning
confidence: 99%